Traços e desenhos da formação profissional: a escolha como processo sob o olhar da política pública no contexto Amazônico (Dados de pesquisa) - Moya, Maria Angélica Dias (2019)
This document is a result of data collected during the implementation of the Focal Group, which was one of the collection techniques used in the master's dissertation on Education, entitled "Traces and drawings of vocational training: the choice as a process under the eyes of public policy in the context Amazonian ". In this way the objective with this is to socialize the collected data. The focus group (GF) was developed from a schedule containing four meetings, scheduled on a day of the week with average duration of approximately two hours. At each meeting a pre-defined theme was addressed. Thus, the themes proposed are as follows: The first is to understand and discuss the role of those responsible, in the process of orienting the choice of the university course for the professional formation of the children, exploring the perceptions of responsible students and teachers. The second discussed the school issue, the actions that have been planned and actually developed as part of its training assignments in the process of choosing the university and the courses for vocational training. The third theme dealt with "the student and his demands", and finally the fourth theme for the labor market in the Amazon region, which ended the process of realization of the GF. The meetings were attended by professionals from educational institutions who, as guests, brought basic information and knowledge to conduct the discussions and support the conduct of the debate. Professionals such as: psychologists, school teachers students, among others. Establish periods. Following the ethical aspects that involve the research with human beings, as recommended in Resolution 510/2016 of the CNS, was secured with the approval of the research in the Committee of Ethics and Research of UFAM - 79104517.0.0000.5020 - CEP UFAM, 2018. Also included were records of the field diary and questionnaires applied to the responsible students.